Continuous Delivery of D-Luciferin by Implanted Micro-osmotic Pumps Enables True Real-Time Bioluminescence Imaging of Luciferase Activity in Vivo - Shimon Gross; Ute Abraham; Julie L. Prior; Erik D. Herzog; David Piwnica-Worms (Molecular Imaging)
Bioluminescence imaging (BLI) of luciferase reporters in small animal models offers an attractive approach to monitor regulation of gene expression, signal transduction, and protein-protein interactions, as well as following tumor progression, cell engraftment, infectious pathogens, and target-specific drug action. Conventional BLI can be repeated within the same animal after bolus reinjections of a bioluminescent substrate. However, intervals between image acquisitions are governed by substrate pharmacokinetics and excretion, therefore restricting temporal resolution of reinjection protocols to the order of hours, limiting analyses of processes in vivo with short time constants. To eliminate these constraints, we examined use of implanted micro-osmotic pumps for continuous, long-term delivery of bioluminescent substrates. Pump-assisted d -luciferin delivery enabled BLI for ⩾ 7 days from a variety of luciferase reporters. Pumps allowed direct repetitive imaging at < 5-minute intervals of the pharmacodynamics of proteasome- and IKK-inhibiting drugs in mice bearing tumors stably expressing ubiquitin-firefly luciferase or IκBα-firefly luciferase fusion reporters. Circadian oscillations in the olfactory bulbs of transgenic rats expressing firefly luciferase under the control of the period1 promoter also were temporally resolved over the course of several days. We conclude that implanted pumps provide reliable, prolonged substrate delivery for high temporal resolution BLI, traversing complications of repetitive substrate injections.